Political Family and Intra-Party Democracy in Indonesia. (A Study on the Political Recruitment of the Golkar Party during the Reform Era in South Sulawesi) - PURWANINGSIH, TITIN; SUBEKTI, VALINA SINGKA (Universitas Muhammadiyah Yogyakarta, 2017)
This paper looks at the political family involved in the local politics in South Sulawesi, particularly the political recruitment mechanism and political party institutionalization from the intra-party democracy perspective. Based on qualitative analysis, the findings of this research show that, firstly, a large number of political families in Golkar Party at South Sulawesi are a product of the oligarchymeritocratic political recruitment. Political legacies such as activities in social and political organizations give more advantages for the political families both in the political recruitment process and the access to power. Secondly, the weakness of Golkar Party’s institutionalization is showed by the dependence of Golkar Party to the party’s elite and the existence of factionalization within the party. As a result of such weakness, several party leaders resign from Golkar Party, thereby strengthening the role of political families in the political recruitment process. 50% of the 2014 electoral vote for the Golkar Party in the South Sulawesi Parliament has been largely contributed by the political families.